Biodiesel from safflower oil and its application in a diesel engine - Ilkilic, Cumali; Aydin, Selman; Behcet, Rasim; Aydin, Huseyin (Elsevier, 2011)
Safflower seed oil was chemically treated by the transesterification reaction in methyl alcohol environment with sodium hydroxide (NaOH) to produce biodiesel. The produced biodiesel was blended with diesel fuel by 5% (B5), 20% (B20) and 50% (B50) volumetrically. Some of important physical and chemical fuel properties of blend fuels, pure biodiesel and diesel fuel were determined. Performance and emission tests were carried out on a single cylinder diesel engine to compare biodiesel blends with petroleum diesel fuel. Average performance reductions were found as 2.2%, 6.3% and 11.2% for B5, B20 and 850 fuels, respectively, in comparison to diesel fuel. These reductions are low and can be compensated by a slight increase in brake specific fuel consumption (Bsfc). For blends. Bsfcs were increased by 2.8%, 3.9% and 7.8% as average for B5, B20 and B50, respectively. Considerable reductions were recorded in PM and smoke emissions with the use of biodiesel. CO emissions also decreased for biodiesel blends while NOx and HC emissions increased. But the increases in HC emissions can be neglected as they have very low amounts for all test fuels. It can be concluded that the use of safflower oil biodiesel has beneficial effects both in terms of emission reductions and alternative petroleum diesel fuel. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Diesel engine; Biodiesel; Alternative fuel; Safflower oil